Implementation of Flutter and Firebase in Bamboo Craft Digitalization Application - Fajar Jati; Suyud Widiono (International Journal Software Engineering and Computer Science (IJSECS), 2025)
: The bamboo craft industry in Brajan Hamlet, Sleman faces significant operational constraints due to continued reliance on manual recording systems, resulting in inefficiency, data duplication, and reporting difficulties. This study develops a web-based digitalization application using Flutter and Firebase to enhance business management efficiency in bamboo craft enterprises. The Research and Development (R&D) method was employed through the Waterfall model across four stages: requirements analysis, system design, implementation, and testing. Data collection involved structured interviews with 6 bamboo craft business operators, 4-week field observations, and literature review. The developed application integrates product management, inventory, transactions, customer relations, and sales reporting features through Backend-as-a-Service (BaaS) architecture utilizing Firebase Authentication, Cloud Firestore, and Firebase Storage. Black Box Testing results demonstrated a 96% functional success rate with an average response time of 1.2 seconds for CRUD operations. User Acceptance Testing with 6 respondents yielded a satisfaction score of 4.3/5 and revealed a 65% reduction in transaction recording time compared to manual methods. However, evaluation identified critical weaknesses in automatic stock synchronization post-transaction, necessitating Firebase Cloud Functions or Firestore Triggers implementation to ensure real-time data consistency. This study offers practical solutions through integrated digitalization for local craft MSMEs while academically demonstrating the effectiveness of Flutter-Firebase integration in developing web-based business management applications, with recognized limitations in business process automation requiring further development.